Effect of War on Health Institutions of Eastern Tigray, Ethiopia - Fikre Belay Tekulu; Haftom Teshale Gebre (Public Health Challenges)
ABSTRACT Background The war in Tigray has caused significant damage to the region's healthcare facilities. This study aimed to assess the extent of the war's impact on healthcare facilities in the Eastern Tigray Zone. Methods A mixed research strategy was used, with both quantitative and qualitative approaches. Primary data were collected through questionnaires, interviews, focus group discussions, and observations, whereas secondary data were obtained from published and unpublished documents. Participants were selected using a simple random sampling method. The collected data were analyzed using a linear regression model to determine the statistical significance of the findings. Results The study found that the impact of the war on healthcare facilities was high to very high, with 97.9% of the damage attributed to the war. Of the 177 healthcare facilities in the Eastern Tigray Zone, 29 (16.4%) were severely affected, and 118 (66.66%) were totally damaged. This indicates that 83% of the health system in the region was damaged. The linear regression model showed that the war explained 55.8% of the observed health facility damage. Conclusions The damage to health facilities in the Eastern Tigray Zone has led to the complete collapse of the health system at the zone level. The urgent need for reconstruction and restoration of health facilities is highlighted to provide essential health services to the affected population. The government and concerned individuals must take immediate action to address this critical situation and help mitigate the negative impact of the war on the health of the people in Tigray.